2023
DOI: 10.26603/001c.73795
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Percussive Therapy On Musculoskeletal Performance And Experiences Of Pain: A Systematic Literature Review

Abstract: Background There is a lack of specific research on the effect of percussive therapy (PT) delivered by massage guns on physiological adaptations. This systematic literature review investigates research conducted on the effects of PT interventions on performance in strength and conditioning settings, and on experiences of musculoskeletal pain. Purpose To determine the effect of PT delivered by massage guns on physiological adaptations: muscle strength, explosive muscle strength and flexibility, and experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…For athletes, percussive therapy has been found to improve muscle endurance and delay muscle fatigue without compromising muscle performance [ 10 , 28 ]. Some studies have also commented on the capacity of percussive therapy to improve explosive muscle strength, a valuable dynamic for athletes, while other studies claim no significant association in this domain [ 6 , 29 ]. The benefits of percussive therapy can impact everyday users in addition to high-performing athletes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For athletes, percussive therapy has been found to improve muscle endurance and delay muscle fatigue without compromising muscle performance [ 10 , 28 ]. Some studies have also commented on the capacity of percussive therapy to improve explosive muscle strength, a valuable dynamic for athletes, while other studies claim no significant association in this domain [ 6 , 29 ]. The benefits of percussive therapy can impact everyday users in addition to high-performing athletes.…”
Section: Discussionmentioning
confidence: 99%
“…A study demonstrated that localized vibrations induced by massage guns at 38 Hz and 47 Hz can increase circulation to the region and therefore aid in the muscle recovery of healthy young athletes [ 52 ]. In the strength and conditioning setting, the use of massage guns allowed for increased muscle strength and explosive muscle performance secondary to delayed fatigue while also reducing musculoskeletal pain perception [ 6 , 10 , 28 , 53 ]. Another study using ultrasound diagnostics found that the use of massage guns on the thoracolumbar fascia resulted in a reduction in echo intensity in that region due to the movement of hyaluronic acid toward the fascial rim and thus improved lubrication and gliding between fascial layers [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations